40.3k views
4 votes
After multiplying each side of the equation by the LCD and simplify , the resulting equation is

After multiplying each side of the equation by the LCD and simplify , the resulting-example-1

1 Answer

6 votes
Answer:


3x^2+20x+12=0


Justification:

1) The LCD is
2 x^(2)

2) The fraction of the left side times the LCD is:


(x^2-x-6)/(x^2) . 2x^2=(x^2-x-6).2=2x^2-2x-12

3) the first fraction of the right side times the LCD is:


(x-6)/(2x) .2x^2=(x-6)(x)=x^2-6x

4) the second fraction of the right side times the LCD is:


(2x+12)/(x) .2x^2=(2x+12)(2x)=4x^2+24x

5) That leads to:


2x^2-2x-12=x^2-6x+4x^2+24x

6) transposing terms to the left and combining like terms:


2x^2-x^2-4x^2-2x+6x-24x-12=0 -3x^2-20x-12=0 3x^2+20x+12=0
User Seyfi
by
6.6k points